ACCOUNTING OF SETTLEMENTS WITH COUNTERPARTIES: SWOT ANALYSIS OF SOFTWARE - Holiachuk Nataliіa (Current Problems of Sustainable Development, 2026)
The article examines the features of the organization of accounting for settlements with counterparties. A list of the main accounting documents used in accounting for settlements with counterparties is provided. The main tasks of accounting for settlements with counterparties are indicated. The need to use software for accounting for settlements with counterparties is substantiated. Software tools of Ukrainian developers used by business structures are characterized, namely MASTER: Accounting, Debit Plus, Accounting SaaS, Dilovod, Bookkeeper, SMARTFIN.UA. The functional capabilities of the named software products and their integration with electronic document management programs and tax reporting services are determined. It is noted that for systematic control of the process of settlements with counterparties, it is advisable to conduct reconciliations and inventory of debt. The features of settlements with counterparties under martial law are indicated. It is proposed to conduct a SWOT analysis of settlements with counterparties, since such an analysis is appropriate in modern conditions of digitalization, is used as a strategic planning tool and allows activating the internal and external resources of the enterprise. A SWOT analysis of the functional capabilities of accounting programs when making settlements with counterparties was conducted. The strengths and weaknesses of software services were identified, as well as their opportunities and threats when carrying out accounting operations. The study found that ERP systems provide deep analytics and a sufficient level of control over settlements, cloud services are characterized by accessibility, ease of use and speed of implementation. It is substantiated that the choice of software for accounting settlements with counterparties should be carried out taking into account the scale of the enterprise’s activities and the complexity of business processes.